Impact of a Series of Educational Talks Taught by Health Professionals to Promote Healthy Snack Choices among Children - Víctor Arufe Giráldez; Javier Puñal Abelenda; Rubén Navarro-Patón; Alberto Sanmiguel-Rodríguez (MDPI AG, 2021)
Background: One of the great challenges facing today's society is the need to combat overweight and obesity in schoolchildren. This study aimed to analyze the impact of a cycle of didactic talks-given to families by a specialist in pediatrics, a specialist in nutrition and dietetics and a specialist in physical exercise-on childrens' snack choices and nutrition quality. Methods: A longitudinal, quasi-experimental and quantitative investigation was designed, working with a total sample of 50 students divided into control and experimental groups. The nutritional quality of daily snacks was recorded during the month before and the month after the cycle of talks given by health experts. Results: An increase in the nutritional quality of the snacks was observed in the days after the talk-but, after a week, values returned to normal. Conclusions: The giving of educational talks to promote healthy habits may have a positive impact on the nutritional quality of school snacks in the days immediately following the talks. However, some forgetfulness was detected over time, which reduced the nutritional quality of the snacks once more. For future work, it is recommended that researchers measure the impact produced by giving regular talks.